Antibiotic susceptibility profile of uropathogens in pregnant women with asymptomatic bacteriuria in tertiary care hospital: a cross-sectional study - K. Murugesh; Harvick P. Gowda; K. Pushpalatha; J. V. Sathish (International Journal of Public Health Science (IJPHS), 2026)
Urinary tract infections (UTIs) are common during pregnancy due to physiological and anatomical changes that predispose women to infections. One such condition, asymptomatic bacteriuria (ASB), if left undiagnosed and untreated, can lead to serious maternal complications such as pyelonephritis, postpartum UTI, and hypertensive disorders, as well as neonatal complications including preterm birth, low birth weight, and intrauterine growth restriction. This study aimed to determine the prevalence of ASB, identify the major uropathogens, and analyze their antibiotic susceptibility patterns in pregnant women, to guide effective antenatal care and treatment. This cross-sectional study was conducted on 100 midstream urine samples, which were cultured using standard microbiological techniques. The bacterial isolates obtained were identified, and their antibiotic susceptibility was determined following standard guidelines. Out of 100 samples, 14 (14%) were positive for significant bacteriuria. The most common isolates were Staphylococcus aureus (42.8%), followed by Escherichia coli (28.6%) and Klebsiella species (28.6%). ASB was most prevalent in women aged 21-30 years (64.3%), during the first trimester (64.2%), and among multigravida women (57.2%). The isolated organisms showed good susceptibility to Ceftazidime/Clavulanic acid, Ciprofloxacin, Vancomycin, Amikacin, Piperacillin–Tazobactam, Imipenem, Teicoplanin, and Linezolid. Early detection and treatment can significantly reduce adverse outcomes, making bacteriuria screening an essential part of routine antenatal care.